Farmer’s agency and institutional bricolage in land use plan implementation in upland Laos - Suhardiman, Diana; Scurrah, N. (Elsevier, 2021)
This paper looks at the (re)shaping of local institutional arrangements within the context of land use planning processes in Laos, bringing to light their dynamic and co-constitutive relationship. Taking Pa Khom village in Houaphan province as a case study, it examines how local tenure institutions are (re)produced, (re)assembled and adapted to mirror farmer’s livelihood strategies to meet households’ food security, while also conforming to the defined land use plan. Drawing on examples of changes in swidden agriculture and village grazing land arrangements introduced as part of land use planning, the paper highlights the important role played by local communities – acting autonomously, collectively and in relation to external agents – in reconfiguring the relationship between natural resources and institutional orders. It illustrates how farmers employ institutional bricolage to creatively assemble and reshape their land use arrangements to comply with the defined land use plan, thus ensuring it meets their locally embedded livelihood priorities, albeit with different distributional outcomes for various farm households. Linking farm households’ strategies with inter-household and village level institutional arrangements, the paper shows how institutional bricolage contributes to synergizing the different rationales behind land use planning processes.